1996
DOI: 10.1017/s1357729800014600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing level of spineless cactus (Opuntia ficus indica var. inermis) on intake and digestion by sheep given straw-based diets

Abstract: 1996). Effect of increasing level of spineless cactus ( Opuntia cus indica var. inermis) on intake and digestion by sheep given straw-based diets. AbstractThe effects of spineless cactus (Opuntia ficus indica var. inermis) supply on digestion of wheat straw was studied n rumen cannulated sheep. In addition to urea (10 g) and mineral and vitamin mixture (30 g), the animals •eceived wheat straw alone or supplemented with graded levels of spineless cactus (150, 300, 450 or 600 g dry natter (DM) per head per day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
0
11

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 8 publications
8
45
0
11
Order By: Relevance
“…Essa característica associada à alta digestibilidade da MS pode ter favorecido o consumo das rações contendo palma, seja na forma de farelo ou in natura, o que corrobora com Sirohi et al (1997) e Ben Salem et al (1996) verificaram aumento no consumo de MS em g/dia e em relação ao peso metabólico, à medida que se elevou o nível de participação da palma em ração para ovinos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Essa característica associada à alta digestibilidade da MS pode ter favorecido o consumo das rações contendo palma, seja na forma de farelo ou in natura, o que corrobora com Sirohi et al (1997) e Ben Salem et al (1996) verificaram aumento no consumo de MS em g/dia e em relação ao peso metabólico, à medida que se elevou o nível de participação da palma em ração para ovinos.…”
Section: Resultsunclassified
“…Tegegne et al (2007), trabalhando com ovinos na Etiópia, avaliou o consumo de água de ovinos alimentados com diferentes níveis de palma forrageira em substituição ao feno de gramíneas nativas (0;20;40;60;80%) e observou efeito linear decrescente da inclusão de palma forrageira sobre o consumo de água. Em trabalhos utilizando palma forrageira, Ben Salem et al (1996) observaram que o volume de água consumido por ovinos diminuiu de 2,4 L da dieta controle (sem palma) para 0,1 L quando o consumo de palma foi maior do que 300g de MS/dia, o que leva a ressaltar a importância dessa forrageira como fonte de água via alimento.…”
Section: Resultsunclassified
“…The yields of non-carcass components in relation to empty body weight were not influenced by the levels of replacement of ground corn by forage cactus meal, except for the yield of the head, which grew linearly (Table 4). According to Berchielli (2006), the development of the digestive tract is associated to the type and quality of the ingested food, indicating that the replacement of ground corn by forage cactus meal did not interfere with the gastrointestinal filling to the point of causing differences in the yield of the digestive tract, and, thus, the levels of forage cactus used had similar yields (P>0.05), although the forage cactus had a lower content of soluble carbohydrates (Menezes et al, 2005) and the content of metabolizable energy decreased as the share of cactus in the diet increased. Rosa et al (2002) affirmed that the gastrointestinal tract has late heterogonic growth, i.e., the longer the termination period of lambs, the more developed it shall be.…”
Section: Resultsmentioning
confidence: 99%
“…The forage cactus meal is a cactus plant considered a vital forage plant in the semiarid region, particularly in the period of rain shortage (Muller et al, 1994), because of its characteristics similar to those of an energy concentrate, such as higher percentage of propionate in the rumen, high level of soluble carbohydrates and high digestibility of dry matter (Ben Salem et al, 1996;Lopes, 2007;Wanderley et al, 2002). Besides, forage cactus meal provides a better pattern of fermentation due to the lower percentage of starch and the higher level of pectin, compared with corn (Van Soest, 1994;Batista et al, 2003;Bispo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Voluntary intake of water by lambs significantly decreased from 1226 ml to 6 ml per day when spineless cactus replaced 80 per cent of the hay in the diet (Tegegne et al, 2007). The digestibility of dry matter, organic matter and crude protein increased with the inclusion of cactus in the diet of lamb (Ben Salem et al, 1996). Previous studies have indicated that spineless cactus could be incorporated in the diet as a replacement for fodder (Gebramariam et al, 2006) or grain (Abidi et al, 2009 andCosta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%